2018
DOI: 10.1109/tuffc.2018.2850535
|View full text |Cite
|
Sign up to set email alerts
|

3-D Velocity and Volume Flow Measurement $In~Vivo$ Using Speckle Decorrelation and 2-D High-Frame-Rate Contrast-Enhanced Ultrasound

Abstract: Being able to measure 3D flow velocity and volumetric flow rate effectively in the cardiovascular system is valuable but remains a significant challenge in both clinical practice and research. Currently there has not been an effective and practical solution to the measurement of volume flow using ultrasound imaging systems due to challenges in existing 3D imaging techniques and high system cost. In this study, a new technique for quantifying volumetric flow rate from the crosssectional imaging plane of the blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Future work should aim to derive WSS from fully 3D measurements of flow by acquiring 4D data, 5,31 by measuring multiple planes 37 or by using speckle decorrelation methods. 36 Despite its limitations we demonstrated that 2D UIV can be used to map TAWSS xz and OSI xz in the abdominal aorta of NZW rabbits. Hence 2D UIV can be used to study the formation and progression of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 81%
“…Future work should aim to derive WSS from fully 3D measurements of flow by acquiring 4D data, 5,31 by measuring multiple planes 37 or by using speckle decorrelation methods. 36 Despite its limitations we demonstrated that 2D UIV can be used to map TAWSS xz and OSI xz in the abdominal aorta of NZW rabbits. Hence 2D UIV can be used to study the formation and progression of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 81%
“…Conventionally, ultrasound speckle is considered as undesirable noise that impacts ultrasound image contrast negatively and a main focus of research has been on the removal of ultrasound speckle 31 . Currently, two ultrasound speckle analysis methods have been studied trying to use ultrasound speckle to resolve flow information, including the cross correlation-based ultrasound imaging velocimetry (UIV) 14,15 and the B-mode intensity-based speckle decorrelation method (SDC) 16,17 . By exploiting dynamic analysis of the normalized first order field autocorrelation function ( 1 ( ) ) of the complex ultrasound quadrature signal, for the first time to the best of our knowledge, we developed the comprehensive vUS theory to accurately measure axial velocity and transverse velocity under different scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we report a novel ultrasound speckle decorrelation-based velocimetry (vUS) method as a quantitative alterative to fUS and a faster velocimetry method than vULM. In contrast to speckle correlation-based ultrasound imaging velocimetry (UIV) 14,15 and Bmode intensity signal-based speckle decorrelation method (SDC) 16,17 , vUS measures the 'angle-independent' directional blood flow velocity by quantifying the decorrelation of the normalized first order temporal autocorrelation function ( 1 ( )) of the complex ultrasound quadrature signal (sIQ). We developed a comprehensive ultrasound-based 1 ( ) analysis theory and data processing methodology for cerebral blood flow velocity measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound speckle decorrelation (SDC) has shown the capability in estimating the through-plane flow velocity using a 1-D array transducer (Rubin et al, 2001, Park et al, 2013, Zhou et al, 2018). With the through-plane velocity, the flow volume can be calculated by integrating the velocity over the luminal area when the vessel is scanned in the transverse view.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the advent of microbubble contrast agents can also significantly enhance the ultrasound signal from blood. Using high frame rate imaging techniques and microbubbles contrast agents, we have recently demonstrated the feasibility of the SDC method both in vitro and in vivo , showing that the maximum measurable through-plane flow velocity can be well over 1 m/s, which is physiologically equivalent to most flow in the cardiovascular system (Zhou et al 2018). However, the current SDC method has an intrinsic limitation on differentiating the flow direction in the blood vessel.…”
Section: Introductionmentioning
confidence: 99%